Process considerations for Product Lifecycle Management implementation for high-value Engineering-to-Order programmes. (10th October 2022) - McKendry, Daniel A.; Whitfield, Robert I.
Abstract: This paper presents the process considerations contained within the first ever framework for implementing Product Lifecycle Management (PLM) within high-value Engineering-to-Order (ETO) programmes. The scientific contribution of the research is the identification of the process-oriented factors that are instrumental in the successful implementation of PLM within an ETO context. The framework has been developed using a qualitative methodology based on the thematic analysis of 27 semi-structured interviews. The participants were senior personnel from 11 ETO organisations in the United Kingdom, France, Australia, the United States and Canada. The thematic analysis resulted in framework themes described in relation to the process objectives, challenges or enablers, and the contributing elements of the themes were then synthesised to illustrate their interconnectedness in supporting PLM implementation. Validation of the framework using 19 participants selected from seven ETO organisations resulted in 95% agreement with statements that assessed the quality, structure and versatility of the framework. This research contributed to the updated BAE Systems Maritime Naval Ships PLM strategy for the design, build and in-service support for the First of Class new generation Royal Navy vessel for a recent shipbuilding programme.